Synthesis Conditions of AgCore@Au Shell System by Laser Ablation with (1064, 532, 355) nm Wave lengths - Ghaleb Al-Dahash (Journal of Global Pharma Technology, 2017)
Laser ablation in liquid technique (PLA) has become a more important for the preparation of NPs. Metal targets were laser ablated in liquid for preparation of spherical Ag @ Au core @ shell NPS colloidal solution for refractive index sensing. In our research was prepared Core-shell Nano colloid system of Ag @ Au by using pulses of Nd-YAG laser with (1064, 532, 355) nm wavelength and (80 @ 60) mJ energy in ethanol liquid. The Surface texture, topography and morphology studied by Transmission Electron Microscopy (TEM) and Scanning Electron Microscope (SEM).Our structural analysis indicated the grains show spherical shape, where TEM images showed formation of Core-Shell clearly, UV-Visible spectroscopy has been employed for the optical properties measurements, Absorption peaks shifted to lower wavelength (blue shift) (UV). The effect of (Ag -core) was more effective than the (Ag - shell), and so by the sliver core effect (Ag -Core), and this confirms clear evidence that the effect of the (Core) influential, which dominates the effect of (shell).